Treatment of neonatal thrombus formation with recombinant tissue plasminogen activator: six years experience and review of the literature. Issue 1 (1st July 2001) - Hartmann, J; Hussein, A; Trowitzsch, E; Becker, J; Hennecke, K-H
Abstract : BACKGROUND: Thrombosis is a relatively rare event in children. However, many conditions in the neonatal period result in an increased risk of thrombus formation. The major risk factor is the indwelling intravascular catheter. Numerous small studies have reported experience of thrombolytic treatment for neonatal thrombotic disease with a wide range of different thrombolytic agents in various forms of administration, dosage, and duration, but no conclusions on the most effective treatment for neonates has been reached. OBJECTIVE: To assess the efficacy and safety of thrombolytic treatment of neonatal catheter related thrombus (CRT) formation with recombinant tissue plasminogen activator (rt-PA). METHOD: Over a six year period, 14 neonates with CRT were treated with the same rt-PA protocol (an initial bolus of 0.7 mg/kg over 30–60 minutes followed by infusion of 0.2 mg/kg/h). RESULTS: Complete clot dissolution was documented in 11 patients, and partial clot lysis in two patients, leading to a patency rate of 94%. In two cases, local bleeding occurred, resulting in treatment failure in one case. Finally, antithrombin III substitution was required in one case. No other complications such as severe bleeding were recognised. CONCLUSION: With the use of close clinical and haematological monitoring on a neonatal intensive care unit combined with serial two dimensional colour echocardiography, the present rt-PA protocol was shown to be a safe and effective method of clot dissolution in neonates.